Laser Face-Lifts: A New Paradigm in Face-Lift Surgery - McMenamin, Patrick (Facial Plastic Surgery, 2011)
Laser-assisted liposuction has been successfully applied to remove fat and contract skin in nonfacial areas. This study evaluated the efficacy and safety of this technique in the face. Patients (n = 40) requesting improvement and a shorter recovery time received one of four laser face-lift (LFL) procedures. The target area was divided into ~15 squares, each around 5 × 5 cm. Each square was treated individually by laser-assisted liposuction to surface temperature end points of 38°C to 40°C. Anatomic areas treated included the submentum, jowls, neck skin, jaw line, cervicomental angle, oral commissures, and nasolabial grooves. Wavelengths were 1064 nm and 1319/1320 nm. Patients returned to their normal lifestyle within 6 to 7 days after treatment. Patient satisfaction was generally higher than that seen in patients receiving a conventional face-lift. Adverse events were limited to burns in two patients. The LFL is a less invasive treatment with acceptable efficacy, reduced downtime, shorter recovery, and lower cost compared with the traditional face-lift.
Keywords: Endolaser; face-lift; laser lipolysis; liposuction